Parallel elementwise processable functions in concurrent clean - Horváth, Z.; Zsók, V.; Serrarens, P.; Plasmeijer, R. (Mathematical and computer modelling, 2003)
The behaviour of concurrent and parallel programs can be specified in a functional style. Functional programming style has some inherent concurrent features. However, for a higher degree of expressing parallelism there is a need for new language constructs. In this paper, we introduce Concurrent Clean modules for evaluation strategies in order to control the evaluation degree, the dynamic behaviour, and the parallelism. The usage of the strategies will be illustrated by the parallel elementwise processing method. The implementation of the method in the lazy functional programming language Concurrent Clean operates with a two arguments two values elementwise processable function. In order to obtain abstract type specification for the generalised manipulation of the linear data structures like lists, arrays, and strict arrays, a linear data structure class module is defined. The programming style is skeleton based. Skeletons in functional languages are higher-order functions. The skeleton given in this paper represents a generalisation of the map function. It is triply parameterized: by an elementwise processable function, by type specification, and by the strategy parameter that defines the dynamic behaviour of the program.